Comparison of productivity and quality of bacterial nanocellulose synthesized using culture media based on seven sugars from biomass. Issue 4 (25th March 2019) - Chen, Genqiang; Wu, Guochao; Chen, Lin; Wang, Wei; Hong, Feng F.; Jönsson, Leif J.
Summary: Komagataeibacter xylinus ATCC 23770 was statically cultivated in eight culture media based on different carbon sources, viz. seven biomass‐derived sugars and one sugar mixture. The productivity and quality of the bacterial nanocellulose (BNC) produced in the different media were compared. Highest volumetric productivity, yield on consumed sugar, viscometric degree of polymerization (DPv, 4350–4400) and thermal stability were achieved using media based on glucose or maltose. Growth in media based on xylose, mannose or galactose resulted in lower volumetric productivity and DPv, but in larger fibril diameter and higher crystallinity (76–78%). Growth in medium based on a synthetic sugar mixture resembling the composition of a lignocellulosic hydrolysate promoted BNC productivity and yield, but decreased fibril diameter, DPv, crystallinity and thermal stability. This work shows that volumetric productivity, yield and properties of BNC are highly affected by the carbon source, and indicates how industrially relevant sugar mixtures would affect these characteristics. Abstract : Komagataeibacter xylinus ATCC 23770 was statically cultivated in eight culture media based on different carbon sources, viz. seven biomass‐derived sugars and one sugar mixture. This work shows that volumetric productivity, yield, and properties of bacterial nanocellulose are highly affected by the carbon source, and indicates how industrially relevant sugar mixtures would affect these characteristics.